2018
DOI: 10.1111/nmo.13289
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater agreement of novel high‐resolution impedance manometry metrics: Bolus flow time and esophageal impedance integral ratio

Abstract: The BFT and EII ratio can be reliably calculated as supported by generally excellent inter-rater agreement. Thus, broader utilization of these measures appears feasible and would facilitate further evaluation of their clinical utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…8 Excellent inter-rater agreement [intra-class correlation coefficient (95% confidence interval) of 0.905 (0.875 – 0.928)] of EII-ratio calculation was recently demonstrated between two raters analyzing 200 swallows from patients with and without achalasia. 14…”
Section: Methodsmentioning
confidence: 99%
“…8 Excellent inter-rater agreement [intra-class correlation coefficient (95% confidence interval) of 0.905 (0.875 – 0.928)] of EII-ratio calculation was recently demonstrated between two raters analyzing 200 swallows from patients with and without achalasia. 14…”
Section: Methodsmentioning
confidence: 99%
“…The overall accuracy is higher than that of the timed barium esophagram. 73,74 Another important value of HRIM is the assessment of esophageal function before surgical fundoplication. Studies have shown that the pressure-flow index, a composite score of three AIM variables, predicts postoperative dysphagia in both adult and pediatric populations.…”
Section: Hrim For Esophageal Dysmotilitymentioning
confidence: 99%
“…Among these are the bolus flow time (BFT) and EII ratio, respectively, predicting flow across the esophagogastric junction (EGJ) or residual due to esophageal stasis as confirmed by studies using simultaneous videofluoroscopy . These advanced HRIM metrics can be reliably calculated as supported by generally excellent inter‐rater agreement . Both BFT and EII ratio have shown promising results in relation to symptom association over other manometric measures among NOD patients .…”
Section: Introductionmentioning
confidence: 96%
“…3,4 These advanced HRIM metrics can be reliably calculated as supported by generally excellent inter-rater agreement. 5 Both BFT and EII ratio have shown promising results in relation to symptom association over other manometric measures among NOD patients. 1,6 However, their application has not been studied in relation to a swallow-by-swallow bolus perception score for different bolus consistencies and volumes and analysis importantly excluded those patients with a HRM diagnosis of EGJ outflow obstruction (EGJOO).…”
Section: Introductionmentioning
confidence: 97%